Exploring the Impact of Secrecy on Marital Happiness: Relationship Authenticity as a Mediator - Bimantara, Marchantya; Karel Karsten, Himawan (Bulletin of Counseling and Psychotherapy, 2024)
Studies investigating the correlation between secret-keeping tendencies and partner satisfaction are still relatively scarce. This research seeks to identify the extent to which the inclination to keep secrets can influence marital satisfaction, with the role of relationship authenticity in unravelling the complexity of such interactions. This study explores the relationship between secret-keeping tendencies and marital satisfaction, with relationship authenticity as a mediator. The research employed a quantitative, cross-sectional methodology utilizing The Five-Item Preoccupation Scale, Authenticity in Relationships Scale, and Relationship Assessment Scale. The study involved 2,184 individuals (76.1% female) aged 25 years and above, all married. The finding reveals that relationship authenticity partially mediates the relationship between secret-keeping tendencies and marital satisfaction. The results of this study can serve as a reference for enhancing marital satisfaction by reducing the inclination to keep secrets and thereby strengthening the perception of relationship authenticity.